Property and power in the early Middle Ages / edited by Wendy Davies and Paul Fouracre. - Davies, Wendy, 1942-; Fouracre, Paul (Cambridge University Press, 1995)
This is a collection of original essays on the relationship between property and power, a fundamental theme in medieval history. It addresses four main issues: the meaning of power over property; the ways in which property conveyed power; the nature of immunities; and the power of royal authority to affect property relations. The areas studied include Wales, England, France, Germany, Italy, and Byzantium, and the essays range across the period 650-1150. A substantial introduction is included, which explains the nature of the issues, and a conclusion expresses the team's overall view of the subject. Aimed at a wide readership of both scholars and students, the volume also includes a glossary to help readers who may be unfamiliar with the material or the period.